VARIATION OF FERROMANGANESE-NODULE COMPOSITIONS WITH TIME IN THE CLARION-CLIPPERTON REGION, PACIFIC OCEAN - Guliy V.N.; Gordiyenko V.V.; Ishchenko V.V.; Sinyukova T.F.; Yanchuk E.A. (My University, 1990)
To determine whether the dynamics of variation in chemical composition of ferromanganese nodules (PMN) depends on their geologic age, the authors used the composition of nodules growing on shark teeth. The latter have already been classified by age so such nodules can now be subdivided into early, middle and late Miocene, Pliocene and Holocene. The teeth and the nodules grown on them were studied by the same method; the tooth was sketched or photographed, described and prepared for analysis, then the chemical composition of overgrowing nodule material was determined. Although the nodule material growing on the oldest shark teeth may be as thick as about 100 to 120 mm, it usually is only half as thick. Judging by the partings enriched in elastic silicate components, the nodule material was deposted intermittently. The authors analyzed material growing directly on the shark teeth.
Keywords: Holocene; Miocene; Pliocene; Cenozoic::Neogene::Miocene; Cenozoic::Neogene::Pliocene; Cenozoic::Quaternary::Holocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Неоген::Миоцен; Кайнозой::Четвертичная::Голоцен